2022
DOI: 10.1002/ana.26368
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Target and Connectivity for Deep Brain Stimulation in Lennox–Gastaut Syndrome

Abstract: Objective Deep brain stimulation (DBS) can reduce seizures in Lennox–Gastaut syndrome (LGS). However, little is known about the optimal target and whether efficacy depends on connectivity of the stimulation site. Using outcome data from the ESTEL trial, we aimed to determine the optimal target and connectivity for DBS in LGS. Methods A total of 20 patients underwent bilateral DBS of the thalamic centromedian nucleus (CM). Outcome was percentage seizure reduction from baseline after 3 months of DBS, defined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 51 publications
3
47
1
Order By: Relevance
“… 11 - 13 In our study, 17 out of 50 had normal brain anatomy and 20 had underlying pathological diseases, and genetic mutations. 11 - 13 …”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“… 11 - 13 In our study, 17 out of 50 had normal brain anatomy and 20 had underlying pathological diseases, and genetic mutations. 11 - 13 …”
Section: Discussionmentioning
confidence: 81%
“… 11 - 13 It was also reported that seizure reduction was achieved after stimulation of anterior, inferior, and lateral borders of the CMN. 13 In the study that was done in Australia, seizure outcomes after 3 months were measured using diaries (52% reduction), EEG (57% reduction), and diary-EEG (44% reduction), EEG and diary EEG were only reported in 17 out of 20 patients because 2 patients mandated lock-down due to COVID-19, while the other 2 studies reported long term follow up data only. 11 - 13 …”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations